2019
DOI: 10.17576/jsm-2019-4806-14
|View full text |Cite
|
Sign up to set email alerts
|

Kesan Penuaan Sesuhu terhadap Sifat Mikro Kekerasan Pempaterian Sn-Ag-Cu/CNT/Cu menggunakan Pelekukan Nano

Abstract: Kesan penuaan terma terhadap sifat kekerasan sambungan pateri Sn-3.0Ag-0.5Cu (SAC305) yang ditambah dengan partikel karbon tiub nano (CNT) telah dikaji. Sifat kekerasan yang menggambarkan kekuatan sambungan pateri ditentukan melalui pendekatan pelekukan nano. Bahan pateri SAC ditambah dengan 0.03% kandungan berat CNT untuk menghasilkan bahan pes pateri SAC-CNT. Pes pateri yang telah dicetak di atas papan litar bercetak (PCB) berkemasan kuprum (Cu) dikenakan pematerian aliran semula pada suhu puncak 260°C untuk… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 15 publications
1
3
0
Order By: Relevance
“…This is due to the indentation size covered both phase area which is near eutectic and β-Sn primary phase. This finding agrees with the other studies, reported that the addition of CNT have a significant effect towards increasing the hardness of solder alloys [28,29,30]. Figure 10 shows the reduced modulus of SAC305 and SAC305 doped CNT solder joint.…”
Section: Resultssupporting
confidence: 91%
“…This is due to the indentation size covered both phase area which is near eutectic and β-Sn primary phase. This finding agrees with the other studies, reported that the addition of CNT have a significant effect towards increasing the hardness of solder alloys [28,29,30]. Figure 10 shows the reduced modulus of SAC305 and SAC305 doped CNT solder joint.…”
Section: Resultssupporting
confidence: 91%
“…In the study, they claimed release of heat rapidly during loading at high strain rates aided in the refinement of grains [24]. The hardness of a material determines its resistance to plastic deformation [25]. In a nanoindentation test, hardness is defined as the sample's ability to withstand the indenter as it penetrates the sample's surface when a load is applied [26].…”
Section: Resultsmentioning
confidence: 99%
“…Hardness is the measurement of the resistance of a material to plastic deformation [12]. Definition of hardness in nanoindentation test refer to the resistance of sample to withstand the indenter as it penetrates the surface of sample when a load is applied.…”
Section: Maximum Depthmentioning
confidence: 99%